Adolescent With 68Ga DOTATATE–Avid Vertebral Hemangioma Mimicking Metastasis in PET Imaging. (July 2015) - Skoura, Evangelia; Alshammari, Alshaima; Syed, Rizwan; Sajjan, Rakesh; Bomanji, Jamshed
Abstract : Abstract: 68 Ga DOTATATE PET/CT is a well-established method in the diagnostic workup of neuroendocrine tumors. We report the case of a 15-year-old adolescent boy with histologically proven appendiceal carcinoid tumor referred for 68 Ga DOTATATE PET/CT to identify residual or metastatic disease. PET images showed increased tracer uptake in the body of T4 vertebra. This uptake could be misdiagnosed for bone metastasis, but CT characteristic appearance was in keeping with vertebral hemangioma. Both bone metastasis in carcinoid tumor and bone hemangiomas in adolescents are rare conditions, but the combined metabolic and morphological information on PET/CT can lead to the correct diagnosis.